Ali Baba and the forty thieves - Munton, Gill. (London : Macmillan education, 2010)
In this classic story, Ali Baba finds a cave full of gold. He is rich! But nothing in life can be so easy. Soon his greedy brother Kasim wants the treasure for himself. Then the forty thieves discover that Ali Baba has been stealing their gold and their leader sets to find and kill him.
Keywords: Readers (Primary); Children's books; Juvenile literature; English language -- Study and teaching